The impact of NBA new rules on games - Nourayi, M. M.; Singhvi, M. (The Sport Journal, 2021)
The purpose of this study is to examine the impact of rule changes by the National Basketball Association on pace, scoring, physicality, and shot selection in professional basketball games. Method: We use regression analysis to examine the trend of various game indicators about the speed and flow, physical plays, shooting accuracy, and shot selection over time. Results: Our findings showed an upward trend in the number of possessions, Points, and Field Goal Attempts in line with the expectation of the NBA league administrators. We also observed a downward trend in the number of Personal Foul calls, Free Throws Attempts, and Free Throws Made after the rule changes and our findings further indicated an increase in relative number of 3-point shots as well as increased shooting precision in 2-point shots. Based on our hypothetical scoring of the games and analysis, about 10.3% of the wins and 6.5% of losses were attributable to 3-point shots. Conclusion: Our analyses indicate that the 2-point shooting percentage (2P%), on average, improved more than that for 3-point shots over time, and the number of personal foul calls, free throw attempts and free throws made declined under new rules over time. Application in Sports: While 3-point shots did not seem to impact the game outcome for most games, it appears that the involvement of the more skilled and agile players has made the game faster. However, shot selection decision by the teams must be based on game conditions and managed by coaches on a game by game basis, perhaps even quarter by quarter, and player by player.